2013
DOI: 10.7224/1537-2073.2012-053
|View full text |Cite|
|
Sign up to set email alerts
|

Natural History of Multiple Sclerosis Symptoms

Abstract: The North American Research Committee on Multiple Sclerosis (NARCOMS) Registry is a database that contains information from over 35,000 patient volunteers on symptom severity in 11 domains commonly affected in multiple sclerosis (MS): mobility, hand function, vision, fatigue, cognition, bowel/bladder function, sensory, spasticity, pain, depression, and tremor/coordination. The Registry affords a unique opportunity to study the frequency and severity of domain-specific impairment in a contemporary, mostly treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
260
3
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(278 citation statements)
references
References 25 publications
5
260
3
10
Order By: Relevance
“…These effects in turn can cause maladaptive responses, such as tendency to be alone and isolated, dissatisfaction with others, and inability to communicate, anxiety, nervousness, and depression (11). A study on patients with MS showed that the patients experienced social and familial outcomes of the disease in 4 realms, familial relationships, social relationships, occupational disruption, and failure to meet living expenses (7).…”
Section: Introductionmentioning
confidence: 99%
“…These effects in turn can cause maladaptive responses, such as tendency to be alone and isolated, dissatisfaction with others, and inability to communicate, anxiety, nervousness, and depression (11). A study on patients with MS showed that the patients experienced social and familial outcomes of the disease in 4 realms, familial relationships, social relationships, occupational disruption, and failure to meet living expenses (7).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of prevalence of self-rated impairment in 11 neurologic domains as a function of disease duration in NARCOMS registrants is presented elsewhere. 29 While maximum ranks of PDDS, displayed in the DET, can help patients and clinicians to better understand disease prognosis, mean ranks (P-MSSS) are more appropriate as an outcome measure in trials and observational studies. For statistical purposes, mean ranks are superior to maximum ranks (cumulative frequency) because, unlike maximum ranks, mean ranks are standardized for differences in the disease duration profiles of the subpopulations.…”
mentioning
confidence: 99%
“…Spasticity is among the most common consequences of MS-induced damage to the central nervous system and is present to some degree in about two-thirds of patients [6,7]. Especially in cases of moderate-to-severe MS spasticity - that is, whenever spasticity causes limitations to mobility, activities of daily living (e.g.…”
Section: Introductionmentioning
confidence: 99%